O desenvolvimento integral das crianças menores de 3 anos na educação infantil - Espego, Gabriela Fernanda (Universidade Federal de São Carlos, 2021)
The discussion made in this work revolves around how we can provide a comprehensive development of children under three years old in Early Childhood Education institutions, aiming to understand and learn from Brazilian works published in the form of scientific articles and books based on the Historical Cultural Theory such as children under three years of age develop and how we can educate them within Early Childhood Education institutions based on the discussions of Historical-Cultural Theory. From the contributions indicated, it is clear how much the presented theory is a fundamental and relevant concept in the world of early childhood education, given that it is a broad theory that contributes to various aspects of child development. The cultural-historical theory is a way to better education, learning and development of students. Whether through educating environments, an environment prepared and thought by the teacher for a rich stimulation of the students' development capacity, or through the games and games that are the main means of learning for these children, we realize that all aspects of that theory bring a view of the subject with potential, and the teacher, having a fundamental role as a mediator in the process, as it is in the effective participation of the student and in the organization of the teaching activity that the possibilities for development are defined.
Early childhood development and education
Keywords: Educação infantil; Teoria histórico cultural; Desenvolvimento integral; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM